Peran Keluarga dalam Pencegahan Stroke pada Pasien Hipertensi di Puskesmas Bendo Kecamatan Pare Kabupaten Kediri - Ria Mislin Asmiarti; Farida Hayati; Linda Ishariani (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2018)
Disease that is a very serious health problem today is hypertension.Hypertension is a major risk factor for stroke. The family was instrumental in determining how the necessary care for sick family member. This study aims to identify the role of the family in the prevention of stroke in patients with hypertension.Researchers used descriptive study. The sample consisted of 41 respondents using purposive sampling technique.Statistical identification using frequency distribution. The results showed the family in identifying problems both hypertension and stroke mostly (70, 7%), family in deciding the appropriate action for the family does not happen stroke mostly(63.4%), the family in providing care sick enough hypertension (68.3% ), family in modifying enough environment nearly half (48,8%), family in using good health service mostly (73,2%).Based on the identification of the role of the family in the prevention of stroke in hypertensive patients enough mostly (58, 5%) due to low income families in providing care and modify the environment. Suggestions from this study is the family is able to search for information on the prevention of stroke in hypertensive patients from the clinic with a diligent control of or from the media to improve in terms of providing care, for example by paying more attention to the family who are sick of hypertension at home and modify the environment, for example in the work of the house of hypertensive patients is charged light work.